Attitude of Nurses Related to The Implementation of Patient Safety in The Intensive Care Unit - Hanik Endang Nihayati; Gunawan Gunawan; Erna Dwi Dwi Wahyuni; Sena Wahyu Purwanza; Hidayat Arifin (Universitas Airlangga, 2019)
Introduction: The error events in the Intensive Care Unit (ICU) were caused by nurses focusing more towards collaborative intervention with other medical staff and workload documentation which was not optimal. The purpose of this study was to determine the predisposing factors related to the implementation of patient safety in the ICU.Methods: This study was a descriptive analytic correlational study. Sample size was determined by purposive sampling and obtained 26 nurses. The independent variables were the predisposing factors and the dependent variable was the implementation of patient safety. Instruments used were a questionnaire and observation sheet. Analysis was performed using Spearman's Rho and Logistic Regression.Results: Spearman’s Rho showed there was a significant correlation between knowledge (p=0.019) and attitude (p=0.040) towards implementation of patient safety. There was no significant of motivation (p=0.073) towards the implementation of patient safety. Logistic Regression showed the dominant factor in implementation of patient safety was attitude.Conclusion: Predisposing factors, that include knowledge and attitude, had a significant effect on the implementation of patient safety, but still required high motivation in the implementation of patient safety. In addition to knowledge and good attitude, nurses are expected to improve motivation in the implementation of patient safety.